URBAN-RURAL TYPOLOGY AND IMPORTANCE OF RURAL AREAS IN EU COUNTRIES - Maja Štrbac; Marko Jeločnik; Velibor Potrebić (Ekonomika Poljoprivrede (1979), 2011)
The European Commission agreed in 2010, on a new typology of regions based on a variation of the previously used OECD methodology. The aim of this new typology is to provide a consistent basis for the description of regions, which the author describes in the paper. The author points out the importance of cooperation with the aim of improving economic activity and quality of life in rural areas of the EU. On the basis of division, the author further analyzes the main indicators for EU member states, such as: territory, population, GVA and employment in all three regions. Based on the results of analysis performed by the conclusion of the importance of rural areas in EU.